KEMUNDURAN BERBAHASA PADA PENDERITA DEMENSIA - Aura Nur Az Zahra; Dona Aji Karunia Putra (Universitas Warmadewa, 2024)
The ability to speak is the greatest gift that God has given to humans. The ability to speak is what distinguishes humans from other living things. Dementia is a disease that can affect a person's memory, thinking ability, behavior, emotions, and language skills. In this article, the author will discuss about one of the language disorders, namely dementia as a language decline. These disorders can affect the way of thinking, making it difficult to express words when communicating. The choice of sentences that are often repeated when speaking is a special sign of people with dementia. Even when communicating, the conversation is often interrupted because people with dementia do not remember what is being said, so they often change topics. This study uses a qualitative method with a descriptive approach, namely the interview and note-taking technique. Sources of data obtained from respondents who are people with dementia.